Novel artifact‐robust and highly visible zinc solid fiducial marker for kilovoltage x‐ray image‐guided radiation therapy. Issue 10 (20th August 2020) - Wang, Tianyuan; Inubushi, Sachiko; Ikeo, Naoko; Mukai, Toshiji; Okumura, Keisuke; Akasaka, Hiroaki; Yada, Ryuichi; Yoshida, Kenji; Miyawaki, Daisuke; Ishihara, Takeaki; Nakaoka, Ai; Sasaki, Ryohei
Abstract : Purpose: To develop a novel biocompatible solid fiducial marker that prevents radiopaque imaging artifacts and also maintains high imaging contrast for kilovoltage x‐ray image‐guided radiation therapy. Methods: The fiducial marker was made of pure zinc. An in‐house water‐equivalent phantom was designed to evaluate artifacts and visibility under various simulated treatment scenarios. Image artifacts were quantitatively assessed in terms of the metal artifact index (MAI) on kilovoltage computed tomography (CT) and cone‐beam CT (CBCT) scans. Marker visibility was evaluated on two types of kilovoltage planar x‐ray images in terms of the contrast‐to‐background ratio (CBR). Comparisons with a conventional gold fiducial marker were conducted. Results: The use of zinc rather than a gold marker mitigates imaging artifacts. The MAI near the zinc marker decreased by 76, 79, and 77 % in CT, and by 77 (81), 74 (80), and 79 (85) % in CBCT full‐fan (half‐fan) scans, when using one‐, two‐, and three‐marker phantom settings, respectively. The high‐contrast part of the zinc marker exhibited CBRs above 2.00 for 28/32 exposures under four (lung, tissue, low‐density bone, and high‐density bone) different simulation scenarios, making its visibility comparable to that of the gold marker (30/32 exposures with CBRs > 2.00). Conclusions: We developed a biocompatible, artifact‐robust, and highly visible solid zinc fiducial marker. Although further evaluation is needed in clinical settings, our findings suggest its feasibility and benefits for kilovoltage x‐ray image‐guided radiation therapy.